Simulation of Full-bore Tube Ruptures in Shell&tube Heat-exchanger - Luigi Raimondi (Chemical Engineering Transactions, 2020)
Shell & Tube heat exchanger is the most often used equipment for heat transfer between fluids in chemical plants, refineries, power generation stations and many other industries. The fluid cooled and the fluid heated are often operated at very different pressures: in this case design standards require an analysis to verify the maximum pressure surge that could be generated by an accidental fluid leak from the high-pressure side of the heat-exchanger into the other. The analysis of such accident is very complex due to a number of interacting phenomena such as vapor-liquid equilibrium, large enthalpy effects, large changes of fluid density and the formation two-phases (vapor and liquid) fluid flows. With reference to a real project case, this article presents the simulation of the pressure increase due to the full-bore rupture of a tube. This evaluation is required to assess if a rupture disk must be installed on the shell side to protect both the equipment and the operating personnel. The analysis is performed using a state-of-the-art dynamic simulation tool.